已知函数,则 f(f(2))= ( )[img=55x35]17a3d9c915d8056.png[/img]
举一反三
- 已知函数[img=55x35]1786a036bbfc5c7.png[/img],则 f(f(2))= ( ) A: 1 B: 2 C: 3 D: 4
- 已知函数y=f(x)在点x=x0处存在极限,且[img=33x31]17e0bf8f4779d17.png[/img]f(x)=a2-2,[img=33x31]17e0bf8f532f434.png[/img]f(x)=2a+1,则函数y=f(x)在点x=x0处的极限为( ) A: -1或2 B: -1或3 C: -1或7 D: -1或9
- 7、二次函数[img=120x26]18031ef2ad3cc4e.png[/img]的对称轴x=2,则f(3)<f(2).
- 函数[img=196x27]17de92706aff834.png[/img],已知f(x)在x=-3处取得极值,则 a等于( ) A: 2 B: 3 C: 4 D: 5
- 函数f(x)=[img=15x18]17e0a6f63edb84a.jpg[/img]-5x-4, 则f′(x)=, f′(2)=.